Red-emitting protein-coated conjugated polymer nanoparticles. Issue 11 (6th October 2016) - Peters, R.; Sandiford, L.; Owen, D. M.; Kemal, E.; Bourke, S.; Dailey, L. A.; Green, M.
Abstract : Red emitting materials are desirable in biology due to the transparency of certain biological tissues at these wavelengths. Abstract : Red emitting materials are desirable in biology due to the transparency of certain biological tissues at these wavelengths. Here, we report the synthesis of aqueous dispersions of amphiphilic protein (hydrophobin) capped red-emitting cyano-substituted poly( p -phenylenevinylene) conjugated polymer nanoparticles (CPNs) and their use in labeling live mammalian (HeLa) cells.